Credit Risk Management Analysis of People's Business Credit (KUR) to Minimize Bad Loans at Bank Mandiri KCP Sidoarjo Candi - Firda Audri Maharani; Sutopo; Ruchan Sanusi (Universitas Bhayangkara Surabaya, 2026)
This study aims to analyze the application of credit risk management in the distribution of KUR at Bank Mandiri KCP Sidoarjo Candi to minimize bad loans. The background is an increase in KUR distribution which has the potential to pose the risk of non-performing loans if not balanced with proper risk management. The research uses a qualitative descriptive method with primary and secondary data, collected through interviews, observations, and documentation. The informants consist of Microservice Officers, Credit Analysts, and Credit Managers, with analysis techniques through reduction, classification, descriptive analysis, and drawing conclusions. The results of the study show that credit risk management is applied through the stages of risk identification, measurement, monitoring, and control. The assessment is carried out from the beginning through character analysis, capacity, business conditions, and the 5C principle, then adjusted to the customer's installment ability. After disbursement, risks are monitored through regular payment evaluation and communication, while control is carried out in stages ranging from monitoring, persuasive approaches, to restructuring. In general, this application is considered effective in reducing the potential for non-performing loans in KUR.